Factors of Low Birth Weight (LBW) Most Related to Stunting in Toddlers - Winastuti, Ambar; Handajani, Sih Rini; Rosalina, Rosalina (Poltekkes Kemenkes Surakarta, 2024)
Background: Stunting is a condition of growth failure in toddlers due to chronic malnutrition, resulting in children being too short for their age, which has an impact on mortality, motor development, and language skills. This study aims to determine the factors associated with stunting in toddlers in Semen Village, Jatisrono District, Wonogiri Regency. Methods: This study used an observational analytical design with a case-control approach. Sampling was conducted using total sampling technique, resulting in 62 respondents. The research instruments were questionnaires and medical records, while data analysis was performed using the Chi-square test and logistic regression to identify the relationship between variables. Results: The results showed that factors significantly associated with stunting were maternal age (χ² = 4.509; p = 0.034), family income (χ² = 5.599; p = 0.018), and low birth weight (LBW) (χ² = 9.378; p = 0.002). The most dominant factor associated with stunting was LBW. The variables of education (χ² = 0.622; p = 0.430), parity (χ² = 0.295; p = 0.587), and exclusive breastfeeding (χ² = 0.081; p = 0.776) did not show a significant relationship. Conclusion: Factors associated with stunting are maternal age, family income, and low birth weight. The most dominant factor associated with stunting is low birth weight. Health workers and village governments can improve nutrition education for expectant mothers, monitor infant growth from birth, and provide special interventions for infants with LBW to prevent stunting.